2014
DOI: 10.4103/0972-5229.133874
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of end tidal and arterial carbon dioxide levels in critically Ill neonates and children

Abstract: Aim of the Study:End tidal carbon dioxide (EtCO2) monitoring is considered to reflect real-time estimation of partial pressure of carbon dioxide in arterial blood (PaCO2) noninvasively. However, knowledge about its relationship with PaCO2 in critically ill pediatric and neonatal patients is limited. The primary objective was to evaluate predictive capability of end tidal carbon dioxide monitoring and secondary objective was to determine the influence of severity of lung disease on EtCO2 and PaCO2 relationship.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…However, Mehta et al found a good correlation at high VI in contrary to our findings, which might be due to small sample size in their study compared with our study (15 vs. 95 pairs). 11 Meredith and Monaco and McDonald et al also found a strong positive correlation (n ¼ 1,708, r ¼ 0.716), and (n ¼ 132, r ¼ 0.79) and a negative impact of severe lung disease, similar to our study. However, both the studies had drawn an average of 17 and eight pairs per patient, respectively, whereas we drew up to five pairs per patient to maintain better validity of coefficient of correlation.…”
Section: Discussionsupporting
confidence: 91%
“…However, Mehta et al found a good correlation at high VI in contrary to our findings, which might be due to small sample size in their study compared with our study (15 vs. 95 pairs). 11 Meredith and Monaco and McDonald et al also found a strong positive correlation (n ¼ 1,708, r ¼ 0.716), and (n ¼ 132, r ¼ 0.79) and a negative impact of severe lung disease, similar to our study. However, both the studies had drawn an average of 17 and eight pairs per patient, respectively, whereas we drew up to five pairs per patient to maintain better validity of coefficient of correlation.…”
Section: Discussionsupporting
confidence: 91%
“…Two other studies report better accuracy of sidestream measurement in a neonatal population . The use of mainstream capnography has been evaluated in a PICU in earlier research, showing that it is a reliable instrument . Also, in studies concerning adult populations, the results are very divers and influenced by multiple parameters .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with normal cardiopulmonary function, there is a good correlation between ETPCO 2 and arterial carbon dioxide pressure (PaCO 2 ); thus, end-tidal capnometry is widely used in clinical practice to estimate PaCO 2 . Today, the end-tidal capnometry has become a basic and standard procedure for respiratory monitoring during anesthesia and recovery,[1415] ICU,[161718] and at emergency departments (ED). [1920] Takano et al studied the utility of the portable capnometer in general wards or in-home care practice in spontaneously breathing patients and reported that expiratory capnometry gives a reliable estimate of PaCO 2 and can be useful to evaluate the respiratory condition of spontaneously breathing patients.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended that blood gases should be measured in these patients until the lung disease is healed. [17]…”
Section: Discussionmentioning
confidence: 99%